Clinical outcomes and programming strategies of implantable cardioverter-defibrillator devices in paediatric hypertrophic cardiomyopathy: a UK National Cohort Study. Issue 3 (22nd November 2020) - Norrish, Gabrielle; Chubb, Henry; Field, Ella; McLeod, Karen; Ilina, Maria; Spentzou, Georgia; Till, Jan; Daubeney, Piers E F; Stuart, Alan Graham; Matthews, Jane; Hares, Dominic; Brown, Elspeth; et al.
Abstract: Aims: Sudden cardiac death (SCD) is the most common mode of death in paediatric hypertrophic cardiomyopathy (HCM). This study describes the implant and programming strategies with clinical outcomes following implantable cardioverter-defibrillator (ICD) insertion in a well-characterized national paediatric HCM cohort. Methods and results: Data from 90 patients undergoing ICD insertion at a median age 13 (±3.5) for primary ( n  = 67, 74%) or secondary prevention ( n  = 23, 26%) were collected from a retrospective, longitudinal multi-centre cohort of children (<16 years) with HCM from the UK. Seventy-six (84%) had an endovascular system [14 (18%) dual coil], 3 (3%) epicardial, and 11 (12%) subcutaneous system. Defibrillation threshold (DFT) testing was performed at implant in 68 (76%). Inadequate DFT in four led to implant adjustment in three patients. Over a median follow-up of 54 months (interquartile range 28–111), 25 (28%) patients had 53 appropriate therapies [ICD shock n  = 45, anti-tachycardia pacing (ATP) n  = 8], incidence rate 4.7 per 100 patient years (95% CI 2.9–7.6). Eight inappropriate therapies occurred in 7 (8%) patients (ICD shock n  = 4, ATP n  = 4), incidence rate 1.1/100 patient years (95% CI 0.4–2.5). Three patients (3%) died following arrhythmic events, despite a functioning device. Other device complications were seen in 28 patients (31%), including lead-related complications ( n  = 15) and infection ( n  = 10). No clinical, device, or programming characteristics predicted time to inappropriate therapy or lead complication. Conclusion: In a large national cohort of paediatric HCM patients with an ICD, device and programming strategies varied widely. No particular strategy was associated with inappropriate therapies, missed/delayed therapies, or lead complications.